Plans for an Italian Antarctic expedition, 1881 - Stone, Ian R.; Bosco, Piero (Polar Record, 2006)
Giacomo Bove, an Italian participant in Adolf Erik Nordenskiöld's 1878–1880 Northeast Passage expedition, and Cristoforo Negri, director of the Italian Geographical Society, drew up plans for an Italian Antarctic expedition to depart from Genoa in 1881. The plans were for a three-year, single-vessel expedition with two winterings, one in the Ross Sea and the second in Enderby Land. They were drawn up in considerable detail and proposed a lavish budget. The expedition never took place because of failure to secure sufficient funds from public subscription and because of the unwillingness of the Italian government to provide support. However, Bove was employed by the Argentine government to put into effect expeditions that had some elements of his plans.